Vegetative desiccation tolerance in Eragrostiella brachyphylla: biochemical and physiological responses. Issue 9 (September 2020) - Yathisha, Neeragunda Shivaraj; Barbara, Plancot; Gügi, Bruno; Yogendra, Kambalagere; Jogaiah, Sudisha; Azeddine, Driouich; Sharatchandra, Ramasandra Govind
Abstract: Eragrostiella brachyphylla is an angiosperm desiccation-tolerant resurrection plant, which can survive during desiccation in the air-dry state and recover completely on availability of water. The present study was conducted to understand the vegetative desiccation tolerance of Eragrostiella brachyphylla by evaluating its ability to recover the physiological, biochemical and morphological functions post desiccation. In order to understand the responses of Eragrostiella brachyphylla to desiccation and subsequent rehydration experiments were conducted in the hydrated state (HS), desiccated state (DS) and rehydrated state (RS). Scanning electron microscopy revealed significant changes between the three stages in the internal ultra-structures of leaves and stems. Compared to the other states, photosynthetic parameters such as chlorophyll a, chlorophyll b, total chlorophylland total carotenoid contents decreased significantly in the desiccated state. Superoxide radical (O2 − ) content also increased, resulting in an oxidative burst during desiccation. Consequently, antioxidant enzymes such as catalase (CAT) superoxide dismutase (SOD) peroxidase (APX) and glutathione reductase (GR) activities were found to be significantly elevated in the desiccated state to avoid oxidative damage. Increased malondialdehyde (MDA) content and relative electrolyte leakage (REL) during desiccation provide evidence for membrane damage and loss of cell-wall integrity. During desiccation, the contents of osmolytes represented by sucrose and proline were found to increase to maintain cell structure integrity. After rehydration, all physiological, biochemical and morphological properties remain unchanged or slightly changed when compared to the hydrated state. Hence, we believe that these unique adaptations contribute to the remarkable desiccation-tolerance property of this plant. Abstract : Plant biology; Desiccation tolerance; RWC; Ultrastructure; Photosynthesis; Antioxidant enzymes; REL; Proline.